A focus group study exploring student nurse’s experiences of an educational intervention focused on working with people with a diagnosis of personality disorder - Stacey, G.; Baldwin, V.; Thompson, B.; Aubeeluck, A. (Wiley, 2018)
Introduction: Negative attitudes exist in practice towards those with a diagnosis of personality disorder. Preregistration training offers the opportunity to address this by developing understanding of the diagnosis, confidence in working with people with the diagnosis and empowering new nurses to challenge prevailing attitudes. Attempts to integrate and evaluate specific educational interventions of this nature into pre‐registration nurse education have not been explored elsewhere. Aim: To explore preregistration nurses’ experience of a programme of training focused on personality disorder and their perception of its influence on attitudes, understanding of clients and their experience of practice. Method: A qualitative study using thematic analysis of two focus groups of pre‐registration mental health nursing students. Results: Evidence of positive attitudes and confidence to supportively challenge negative attitudes in practice were found. Students showed a shift away from a focus on changing the perceived ‘difficult’ behaviour of a client towards an understanding of their own emotional responses to the behaviours. Discussion: The Knowledge and Understanding Framework training shows potential for students to change attitudes and develop progressive practice working with people with personality disorder. Implications for Practice: The integration of the Knowledge and Understanding Framework should be considered as part of preregistration training. Further research into the sustained influence of the training post registration is required.